Germanizmy leksykalne w gwarze miejskiej Poznania i brneńskim hantecu - Osowski, Błażej (Slavia Occidentalis, 2013)
The article offers a comparison of lexical Germanisms which occur in the urban sub-dialects of Brno and Poznań, two cities located at a significant distance from each other. The analysed vocabulary has been divided into: A) words which are part of the general German language, B) words which could not be classified as German due to the following criteria: a) chronological, b) stylistic, c) limited territory, d) unofficial nature and e) social. The analysis has demonstrated that, despite there being no contact between the two cities, as many as 32 words (preferences) in the sub-dialects have identical or similar meaning.